STUDIO DI ENZIMI D’INTERESSE MEDICO ED INDUSTRIALE - Fogal, Stefano (Università degli studi di Padova, 2010)
Three main projects were carried out in the time span of my doctorate. Two of them consist in the identification of enzymes necessary to perform mid- or final steps in drugs preparation; the third is related to recombinant human tyrosinase expression, partial purification and characterization. In collaboration with Fabbrica Italiana Sintetici (FIS), a critical step in the synthesis of a Moxifloxacin building block has been identified. An alternative enzymatic route is proposed that allows the resolution of a dicarboxylic esters racemic mixture. To this aim an enzyme that selectively hydrolyse one of the two enantiomers was searched. More precisely we aimed to use this enzyme to produce an enantiopure acid form, easy to separate from the unreacted enantiomer by organic phase extraction and used the desired enantiomer to prepare the Moxifloxacin building block (4as,7as)-ottaidro-1H-pirrolo[3,4-b]piridina. After trying several commercially available enzymes that have as substrates racemic mixtures, using different analytical approaches (NMR and HPLC-MS techniques), we succeeded in finding Candida antarctica lipase B as a highly selective enzymes that partially hydrolysed the mixture of dimethyl 1-acetylpiperidine-2,3-dicarboxylate in aqueous buffer. Enantiomer selectivity was evaluated by chiral HPLC analysis on a preparative scale, confirming that hydrolysis produces a high enantiomeric excess of the 2R, 3S form. Furthermore, MS analysis confirmed that only one of the two methyl esters was hydrolyzed by the lipase, conferring at the enzyme regioselectivity too. The reaction product was further characterized by NMR techniques (COSY, HMQC, HMBC), which indicate that hydrolysis take place on methyl group in position 3. Kinetics analysis by NMR was used to estimate the values of Km and Vmax of the hydrolysis reaction. The enzyme was used by FIS for grams-scale Moxifloxacin precursor synthesis. This process has been submitted for patent. A second project, again in collaboration with FIS, was focus on overcoming a ...